(Bez)sens planowania przyszłości... Refleksje o adolescencyjnym projektowaniu przyszłości edukacyjno-zawodowej - Piorunek, Magdalena (Wydawnictwo Naukowe UAM, 2011)
The text Sense(lessnes) of future planning... Reflections on educational and vocational future planning by adolescents poses a question about whether the planning of educational and vocational future by adolescents makes any sense and is effective in the post-modern times, when the social reality is ambiguous, unpredictable, unstable and changes dynamically. The author makes references to the original research of the educational and vocational future planning process by adolescents and provides us with the characteristics of the future planning styles and strategies that were identified in the longitudinal and cross-sectional studies. The author considers how young people cope with answering the identity-crisis specific questions of Who am I and Who shall I be in the future. The qualitative characteristics presents young people applying the present-oriented and future-oriented strategies in the approaches to their educational and vocational carriers. References are also made to a reflection, a central one in the carrier guidance, on how effective the educational and vocational guidance can be in the situation of permanent change and apparently rational behaviour of adolescents who choose not to plan.
Sense(lessnes) of future planning... Reflections on educational and vocational future planning by adolescents
Keywords: planning of educational and vocational (professional) future; adolescence; contemporary youth empirical studies; vocational counseling (guidance)